How Participatory is Participatory Irrigation Management - Souvik Ghosh , P. S. Brahmanand , K. G. Mandal , P. Nanda and D. U. Patil, (Indian Journal of Extension Education, 2016)
An assessment of Participatory Irrigation Management (PIM) was carried out in Kuanria Medium Irrigation Project inNayagarh district of Odisha covering 10 WUAs with a sample survey of 350 farmers. Methodologies developed to assessfarmers' perceptions towards extent of participation, utility of irrigation service and performance of water user association(WUA) in the command area (varied from 274.95 ha to 501.70 ha) under the WUAs. Overall participation of the farmerswas below average in case of all the 10 WUAs as evident from lower farmers' participation index values (